Sociodemographic and Digital Education Factors Are Associated to General Health, Coping Strategies, and Academic Outcomes of Undergraduate Students during the Post-Pandemic Period - Luigi Tinella; Andrea Tinterri; Anna Dipace; Manuela Ladogana; Isabella Loiodice; Andrea Bosco (MDPI AG, 2022)
The COVID-19 pandemic suddenly and forever changed the lives of many undergraduate students around the globe, forcing them to switch to online learning while undergoing social confinement within their homes. It is now well-established that this prolonged period of uncertainty impacted students' well-being, health, and academic achievement. However, how student-related factors, such as coping strategies as well as sociodemographic, contextual, and technological variables, are linked to digital education factors is currently less understood. Using multiple regression analysis, this study investigates the results of an online questionnaire administered to students from two universities in southern Italy, differing in positioning and size, as well as policies and attitude towards digital learning. The results of this study show the positive effects of expertise with digital devices and university digital learning policies on students' perceived general health. Conversely, isolation and lack of relational connectedness negatively impacted students' health. Furthermore, this study highlights the role of different coping strategies, demonstrating that active forms of coping have a positive effect on students' health, whereas avoidance strategies have the opposite effect. Taken together, this study provides crucial links between the many factors influencing students' experience with online learning and health, and provides useful indications to promote the uptake of and adaptation to online learning.